LEGAL REGIME OF THE AUTHORIZED CAPITAL OF BUSINESS ENTITIES: THEORETICAL AND METHODOLOGICAL FOUNDATIONS AND LAW ENFORCEMENT ISSUES (Eureka Journal of Humanities and Social Research, 2026)
This article presents a comprehensive legal analysis of the legal regime of the authorized capital as a fundamental institution of corporate law. The author examines the dual nature of the authorized capital, serving simultaneously as the material base of an enterprise and as a legal instrument for protecting the interests of creditors. The functions of the authorized capital fund are critically reconsidered in the context of the liberalization of the Republic of Uzbekistan’s corporate legislation. Special attention is given to the defects in the legal regulation of non‑monetary contributions and the problem of maintaining equivalence between the declared capital and the actual net assets of the company. Based on the results of the study, proposals are formulated for implementing mechanisms of subsidiary liability for undercapitalization and for digitizing control over the state of assets.
Keywords: Authorized capital; business entities; civil law; legal regime; corporate governance; net assets; guarantee function; non‑monetary contributions; legal entity; liability of participants.